Leg heating and cooling influences running stride parameters but not running economy - Folland, J. P.; Rowlands, D. S.; Thorp, R.; Walmsley, A. (International Journal of Sports Medicine, 2006)
To evaluate the effect of temperature on running economy (RE) and stride parameters in 10 trained male runners (V·O2peak 60.8 ± 6.8 ml · kg-1 · min-1), we used water immersion as a passive temperature manipulation to contrast localised pre-heating, pre-cooling, and thermoneutral interventions prior to running. Runners completed three 10-min treadmill runs at 70 % V·O2peak following 40 min of randomised leg immersion in water at 21.0 °C (cold), 34.6 °C (thermoneutral), or 41.8 °C (hot). Treadmill runs were separated by 7 days. External respiratory gas exchange was measured for 30 s before and throughout the exercise and stride parameters were determined from video analysis in the sagittal plane. RE was not affected by prior heating or cooling with no difference in oxygen cost or energy expenditure between the temperature interventions (average V·O2 3rd - 10th min of exercise: C, 41.6 ± 3.4 ml · kg-1 · min-1; TN, 41.6 ± 3.0; H, 41.8 ± 3.5; p = 0.94). Exercise heart rate was affected by temperature (H > TN > C; p < 0.001). During minutes 3 - 5 of running the respiratory-exchange and minute ventilation/oxygen consumption ratios were greater in cold compared with thermoneutral (p < 0.05). Averaged over the full 10 min of exercise, stride length was shorter and stride frequency higher for the C trial compared to TN and H (p < 0.01). Leg temperature manipulation did not influence running economy despite changes in stride parameters that might indicate restricted muscle-tendon elasticity after pre-cooling. Larger changes in stride mechanics than those produced by the current temperature intervention are required to influence running economy.